Saberes e fazeres da equipe técnica no sistema socioeducativo em meio aberto no município de Manaus: “as(os) especialistas são vocês!” Knowledge and practices of the technical team in the non-custodial socio-educational system in the city of Manaus: “The experts are you!” - (:unkn) unknown (Universidade Federal do Amazonas, 2020)
This research focuses on the practices of psychosocial teams that assist adolescents in compliance with socio-educational measures in an open environment at CREAS [Specialized Reference Centers for Social Assistance] in Manaus, Amazonas. Although non-custodial measures are preferable to restricting freedom they are characterized by the complexity of their operationalization, resulting in uncertainties on the part of the team about the effectiveness of the actions developed. From the execution of the project “Socio-education Experiences Space”, which promoted meetings between professional teams where they problematized their work, exchanged experiences and jointly built proposals aimed at solving some of their demands, another study was proposed. This had the objective of understanding the practices of these professionals, from the confrontation they carry out on their own, highlighting the potential and fragility of their actions, focusing on the movements of change in order to overcome difficulties. Based on the theoretical framework of Historical-Cultural Psychology and the Clinic of Activity, a qualitative research was proposed, through simple and cross-team confrontations with professionals from the city’s five existing CREAS. In these sessions, participants evaluated their own and their peers’ practice. Subsequently, adolescents, who were attended by the teams, were interviewed about the actions of the professionals responsible for monitoring the measure. As a result, it was observed that new discursive frameworks to welcome and understand the potential and fragility of socio-educational actions at different moments of the adolescent's journey were created. With the aid of Grounded Theory to analyse the data, an integrative hypothesis was built that shows that the practice is mediated by instruments and by the legal-institutional prescription, with the presence of factors that interfere negatively in the fulfillment of the measure. However, due to the demands of the reality of the practice, the professionals present variations of style that at different times either renew or maintain the professional genre, in order to overcome the difficulties of doing the work and expand the power to act individually and collectively. It was concluded that the self-confrontation method generates participatory involvement of professionals, a fundamental factor in the reflective process; understanding of work instances; development of work teams and understanding what defines the Professional genre, as presented by Yves Clot. Emphasis is given in the integrative hypothesis to the mediation of instruments in all spheres and relationships concerning the socio-educational process, the creativity of the team in transforming their actions and the bonds established between professionals and young people. The statements of the adolescents served by the teams corroborate that the actions of the teams build a favorable environment, that promotes changes in the lives of those who comply with non-custodial socio-educational measures.
Keywords: Medida socioeducativa em meio aberto; Psicologia do adolescente - Pesquisa; Centros de Referência Especializados de Assistência Social de Manaus; Psicologia Histórico-cultural; Transgressão da lei; CIÊNCIAS HUMANAS: PSICOLOGIA: PSICOLOGIA SOCIAL; Adolescente em conflito com a lei; Equipe psicossocial; Autoconfrontação; Clínica da Atividade; Medidas socioeducativas em meio aberto